Total and Subtotal Parathyroidectomy in Young Patients With Multiple Endocrine Neoplasia Type 1-Related Primary Hyperparathyroidism: Potential Post-surgical Benefits and Complications - Tonelli, Francesco; Marini, Francesca; Giusti, Francesca; Brandi, Maria Luisa (Frontiers in Endocrinology, 2018)
Background: The choice of surgical treatment for patients with Multiple Endocrine Neoplasia type 1 (MEN1)-related primary hyperparathyroidism (PHPT) remains controversial and it has not been specifically addressed in young patients. Methods: This is a retrospective case series study. The study includes the surgical data and the follow-up of 38 patients younger than 30 years of age, all diagnosed with MEN1, collected and followed-up between 1991 and 2017 at the Regional Referral Center for Inherited Endocrine Tumors of the Tuscany Region, and operated by parathyroidectomy. Genetic and/or clinical MEN1 diagnosis was made before surgery in all patients. Subtotal (9/38 patients) or total parathyroidectomy with auto-transplantation (28/38 patients) were performed in all patients but one, in whom a single mediastinal adenoma was excised from the aorto-pulmonary window. All patients but one, who was operated in 2017, had a post-operatory follow-up of at least 12 months. Results: Total parathyroidectomy (TPTX), with auto-transplantation, was the most frequently adopted operation both as primary (20/38 patients) and secondary (8/38 patients) surgery, followed by subtotal parathyroidectomy (SPTX; 9/38 patients) and limited parathyroidectomy (1/38 patient). At follow-up, lasting a mean of 11.8 + 6.6 years (range 0-23 years), no persistent PHPT was observed. PHPT recurred in 4/28 TPTX (14%) and in 2/9 SPTX (22%). Permanent hypoparathyroidism showed no statistically significant difference between the procedures (2/9 in SPTX and 5/28 in TPTX). Conclusions: Data from this retrospective study showed the efficacy of TPTX for the treatment of MEN1-PHPT, also in adolescent and young patients, showing, in our series, no risk of PHPT permanence and a longer disease-free period and, subsequently, the possibility to postpone re-intervention with respect to both limited PTX and SPTX. The risk of permanent hypoparathyroidism in TPTX was comparable to STPX, and could be mitigated over the years.